Cytotoxicity of Calcium Hydroxide on Human Umbilical Cord Mesenchymal Stem Cells - Eric Priyo Prasetyo; Ira Widjiastuti; Febriastuti Cahyani; Mefina Kuntjoro; Nike Hendrijantini; Ninuk Hariyani; Ervina Restiwulan Winoto; Alexander Patera Nugraha; Sianiwati Goenharto; Helen Susilowati; Eryk Hendrianto; Fedik Abdul Rantam (Association of Support to Oral Health Research (APESB), 2022)
Objective: To examine the cytotoxicity of calcium hydroxide on human umbilical cord mesenchymal stem cells (HUCMSC) to understand the characteristics for use in regenerative dentistry procedures especially regenerative endodontics. Material and Methods: HUCMSC was isolated, cultured, and confirmed by flow cytometry. The biological characteristics, such as cell morphology, proliferation, and protein expression, were screened. To check the cytotoxicity, HUCMSC was cultured and divided into two groups, the control group (cultured in minimum essential medium (MEM) alpha) and calcium hydroxide group (cultured in MEM alpha and calcium hydroxide). Methyl-thiazole-tetrazolium (MTT) assay was done on different concentrations of calcium hydroxide (0.39 to 25 µg/mL) and the cells were observed and counted. One-way ANOVA test was used with a significance level set at 5%. Results: Flow cytometric analysis confirmed positive of CD73, CD90, CD105, negative of CD45 and CD34. A significant difference was found between the concentration of 6.25 and 3.125 µg/mL (p=0.004). There was no significant difference among 6.25, 12.5 and 25 µg/mL concentrations. There was also no significant difference among 0.39, 0.78, 1.56, and 3.125 µg/mL concentrations. Conclusion: Even though calcium hydroxide is a medicament of choice in clinical endodontics, it decreases the viability of HUCMSC. The lower the concentration of calcium hydroxide, the higher the viability of HUCMSC.